Factors of enterprises’ innovative susceptibility - Ulybyshev, D.N.; Petrenko, Ye.S.; Zhailauov, Ye.B.; Kenzhebekov, N.D.; Kabdybay, A.K. (BUKETOV BUSINESS REVIEW, 2020)
Object: To explore the conceptual basis for determining the innovative susceptibility of economic actors and their influence factors. Methods: The methodological basis of the study was evolutionary theory of economic growth, concepts of innovation process and innovative susceptibility. Methods of systematic and institutional analysis of processes of perception of innovation in national and regional innovation systems were used. Results: Exogenous (type of economic system, openness of economy, place in the international division of labor) and endogenous (competition, institutions, innovative potential) factors of innovative development have been identified. Exogenous factors do not depend directly on the activities of the firm, and often overall state, but the dynamics of these factors should be taken into account in the process of implementation of both innovation policies of the state and innovation projects of the firms. More important for entrepreneurs are endogenous factors. At the same time, it is necessary to take into account that the main part of potential innovative shifts is created in the sphere of generation of new knowledge, where human activity is determined not by technological logic of production, but by laws and incentives of creative process. In this regard, the fundamental feature of internal factors of innovative development is that a new variable is introduced - intellectual capital, characterizing the volume of accumulated scientific knowledge and practical experience. A detailed assessment of innovation susceptibility factors allows them to be classified by place of origin within the existing innovation process: environmental factors, business factors, legal regulatory factors, social factors and science factors. Conclusions: Identification of factors of innovative susceptibility of economic relations subjects allows defining parameters of innovative interaction of innovative companies with external and internal elements of innovation process.